2016
DOI: 10.1515/cdbme-2016-0148
|View full text |Cite
|
Sign up to set email alerts
|

From imaging to hemodynamics – how reconstruction kernels influence the blood flow predictions in intracranial aneurysms

Abstract: Abstract:Computational fluid dynamics (CFD) is increasingly used by biomedical engineering groups to understand and predict the blood flow within intracranial aneurysms and support the physician during therapy planning. However, due to various simplifications, its acceptance remains limited within the medical community. To quantify the influence of the reconstruction kernels employed for reconstructing 3D images from rotational angiography data, different kernels are applied to four datasets with patient-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Since O’Meara et al 13 showed that the algorithm used for image reconstruction is a significant parameter, it was the focus of this study. Its importance with respect to the intra-aneurysmal flow is confirmed by the results of this study, which was motivated by findings of a preliminary work 14. These were based on 3D-DSA, reconstructed with two different kernels and three different image characteristics.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Since O’Meara et al 13 showed that the algorithm used for image reconstruction is a significant parameter, it was the focus of this study. Its importance with respect to the intra-aneurysmal flow is confirmed by the results of this study, which was motivated by findings of a preliminary work 14. These were based on 3D-DSA, reconstructed with two different kernels and three different image characteristics.…”
Section: Discussionsupporting
confidence: 65%
“…Next, a representative slice of the 3D DSA data comprising the aneurysm was selected and threshold values for the remaining reconstruction kernels were manually adapted such that the resulting isocontours matched the reference segmentation (see online supplementary table S1). Online supplementary figure 1 illustrates the segmentation process (see also Glaßer et al 14 for further details).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We extracted a 3D surface model in accordance with Saalfeld et al 12,13 using 3D rotational-angiography and magnetic resonance angiography datasets. For morphological analysis, we applied a semiautomatic approach, which allows the automatic determination of 21 parameters based on the reconstruction of the neck curve 14 (Table 2).…”
Section: Morphology and Hemodynamicsmentioning
confidence: 99%
“…Such surface-based colon data processing methods highly depend on the quality of the reconstructed colon surface, such that it is without topological noises or errors. With the rapid advances in data acquisition techniques in recent decades, high resolution of three-dimensional data has been produced for various applications, including real-time vision processing [10], industrial application [11], textured 3D mesh generation [12], blood flow simulation [13], cardiac structure reconstruction [14], robotic 3D reconstruction of an object [15], ceramics analysis and reconstruction [16], and unmanned-aerial-vehicles-based 3D reconstruction [17], etc. However, many existing surface reconstruction methods introduce topological noises or errors into the resulting reconstructed surfaces, which makes it intractable to perform subsequent computation tasks, such as surface simplification and parameterization.…”
Section: Introductionmentioning
confidence: 99%